THE FLEXIBLE TUNNEL LINING IN DIFFICULT MINING AND GEOLOGICAL CONDITIONS - Druzhko, E. B.; Ogloblin, V. F.; Samoylov, V. V. (Science and Transport Progress, 2010)
The article is dealt with the issues of efficiency and constructive solutions to nodes and elements of the lining objects of tunnel type in complicated geological conditions. A construction of the lining from the universal yielding blocks of uniform size is offered. Reaching pliable layer and methods of calculating of the veering capacity of a two-layer lining arched and circular shapes are recommended.